EUPHEMISMS IN POLITENESS PRINCIPLE - Rabiyeva, M.G‘; Davronova , G.I (Innovative Development in Educational Activities, 2023)
Euphemism is a kind of effective language form used in communication, which aimed to produce reasonable communicative effect. This article provides an information about euphemism and scholar’s opinion about it. In addition, the relation between euphemisms and politeness principles is explored.